Sentinel Lymph Node Biopsy Is Feasible in Dogs with Scars from Prior Local Excision of Solid Malignancies - Elisa Maria Gariboldi; Damiano Stefanello; Mirja Christine Nolff; Donatella De Zani; Davide Zani; Valeria Grieco; Chiara Giudice; Camilla Recordati; Francesco Ferrari; Roberta Ferrari; Lavinia Elena Chiti (Animals, 2022)
Sentinel lymph node (SLN) biopsy is a well-established staging tool in canine oncology. This study aims to explore the feasibility of SLN biopsy in dogs with scars from prior excised solid malignancies that were referred for further tumor staging and/or adjuvant treatment options. Mapping was either performed using radiopharmaceutical, methylene blue, and/or near-infrared fluorescent (NIRF) imaging. Thirty-three dogs with 34 scars from prior excision of the mast cell tumor (MCT) (n = 29), soft tissue sarcoma (n = 2), oral melanoma (n = 1), subungual melanoma (n = 1), and mammary adenocarcinoma (n = 1) were retrospectively enrolled. Primary treatment consisted of curative intent/wide tumor excisions in 50.0% of dogs and marginal excision in the remaining 50.0%. The median time between tumor excision and SLN biopsy was 50 days (range 17–110 days). The procedure was successful in 31/34 scars, translating to a detection rate of 91.2%. The SLN did not correspond to the regional lymph node in 19/31 scars (61.3%). SLN metastases were histologically identified in 13/31 (41.9%) dogs, all of them affected by MCT. Based on our results, SLN biopsy using lymphoscintigraphy/methylene blue and/or NIRF is feasible in dogs presenting with scars from the prior surgical excision of solid tumors, and should be suggested for accurate nodal staging.